International protection for human rights activists - حميد, سعد ناصر (Journal of Legal Sciences, 2021)
Despite the primary role of governments in assuming the primary responsibility in protecting human rights in accordance with international human rights standards and instruments, they are not the only party responsible for ensuring the implementation of those rights. Individuals themselves have a duty towards their society to observe, respect and promote those rights and freedoms and work to protect them by means. All, and this is confirmed by Paragraph (1) of Article (29) of the Universal Declaration of Human Rights of 1948, which states: “Every individual has duties towards the society in which it is only possible for his personality to grow freely and fully.                                               Throughout history, many individuals and groups emerged, whether at the international or national level and with their different names “activist, defender, worker, observer” who had a great and effective role in calling for the implementation and activation of human rights in their societies, and they paid their lives and freedoms for that, as well as for Restrictions, intimidation, and monitoring by various means to limit their effectiveness, we mention the human rights activist "Martin Luther" and the activist "Nelson Mandela", who spent their lives fighting racial discrimination                                                                .              On the other hand, we find that there is no real endeavor by governments to deal with the attacks that affect them or a political will to protect them as an important component of the necessary components to create a more secure and just world, especially in our beloved country, and the international community later alerted the importance of the role that individuals play in that aspect, and the need to provide International protection for them, when the United Nations General Assembly in 1998 adopted by consensus the declaration on the "right and responsibility of individuals, groups and community organizations to promote and protect universally recognized human rights and fundamental freedoms", which was a major step as it gave the activist legal status, powers and rights in addition to being between Protection measures that must be adopted by states.                                       Therefore, through our research we sought to identify the human rights activist, the statement of the international legal status and the international and national protection mechanisms available to activists, as well as shed light on the most prominent obstacles, challenges and violations that faced their work, and we reached in conclusion a set of results, the most important of which are:                      1.The 1998 Declaration on the Rights of Human Rights Defenders represents an important achievement at the international level, as it recognizes the defense of human rights as a right in itself, and has granted activists in the field of human rights defense an important legal positionto conduct their work.                                                                           2.Take the necessary measures to ensure that the laws in force, such as those related to security, are not abused to restrict the work of activists and limit their freedom, including Article (200) and Paragraph (5) of Article (372) of the Iraqi Penal Code in force of 1969  .